Manufaktur Palu Plastik 300g, Panjang 30 cm, Diameter 5 cm, Pegangan Kayu, Kapasitas 5 Biji/Jam - Kurnia Widya Pratama Adesurya; Syamsul Hadi; Candra Aditya Nanda Putra; Armano Maulana Kaka; Dimas Arya Putra (Jurnal Kendali Teknik dan Sains, 2026)
The problem lies in the scarcity and relatively high price of 300 g plastic hammers on the market. The manufacturing goal is to obtain a 300 g plastic hammer, 30 cm long, 5x4 cm oval diameter, with a wooden handle. The manufacturing method includes: design of a plastic head mold for one mold to produce two pieces; design of a steel mold for casting T-joints made of aluminum which are inserted with 2 M10 steel bolts with a length of 15 mm before casting; preparation of polypropylene (PP) plastic material by adding 10% used PP plastic and giving pigment colors according to order; PP injection molding at a temperature of 160oC, duration of 12 minutes; order of a wooden handle from a professional wood craftsman; assembly of a plastic hammer with a T-shaped aluminum casting; trial beating on a rubber block for thread bond inspection; finishing; quality-dimensional inspection. The manufacturing results are in the form of a polypropylene plastic hammer with a total weight of T Aluminum and 2 plastic hammer heads of 300 g (without wooden handles), a total length of 30 cm, an oval diameter of 5x4 cm, a manufacturing cost of IDR 70,000/unit and a manufacturing duration of 12 minutes/unit which has the consequence that the 300 g plastic hammer can be used for hitting metal without damaging its surface, especially for small movements in adjusting components or workpieces during machining or assembly.